SIMULASI KUALITAS AIR PADA SISTEM DISTRIBUSI AIR WILAYAH PELAYANAN IPA AURDURI 3 MENGGUNAKAN SOFTWARE EPANET 2.2 - Gusri, Lailal; Ilfan, Freddy; Septian, Ahmad Al Idrus (EnviroScienteae, 2024)
This research aims to model residual chlorine in the drinking water distribution system with EPANET 2.2 software in the IPA Aurduri 3 of service area. The problem that occurs is the construction of the Aurduri 3 IPA in 2020 to meet the need for clean water in several areas that are not reached by the Aurduri 1 IPA and 2, especially the Bougenville, Pinang Merah and surrounding areas. Adding chlorine twice, namely at the IPA Aurduri 3 and the booster pump, increases the risk of excess chlorine in the service area and can reduce water quality. Modeling the distribution of residual chlorine in the clean water distribution system can provide a solution in dealing with residual chlorine in drinking water distribution. The results found of 30 points in the clean water network that were below standard and dominated at the service end with residual chlorine ranging between 0-0.4 and after calibration 0.16-0.3. This is due to the age of the water which is influenced by velocity which does not meet the standard by 121 points and causes delays in obtaining residual chlorine at sufficient levels.